Extended release and enhanced bioavailability of moxifloxacin conjugated with hydrophilic cellulose ethers. (20th January 2016) - Abbas, Nazia S.; Amin, Muhammad; Hussain, Muhammad A.; Edgar, Kevin J.; Tahir, Muhammad N.; Tremel, Wolfgang
Graphical abstract: Highlights: Prodrug design of moxifloxacin based on cellulose ether derivatives. Moxifloxacin prodrugs showed self-assemblies at solvent interface. Extended drug release of moxifloxacin from prodrugs. Enhanced bioavailability of moxifloxacin from prodrugs. Abstract: Macromolecular prodrugs (MPDs) of moxifloxacin were fabricated based on hydroxypropylcellulose (HPC) and hydroxyethylcellulose (HEC). UV/Vis spectrophotometry was employed to determine covalently loaded drug content (DC) of each conjugate. The degree of substitution (DS) of moxifloxacin attained ranged from 0.27 to 0.38 (HPC) and 0.19 to 0.26 (HEC) per anhydroglucose unit (AGU), respectively. Transmission electron microscopic analyses showed that HPC–moxifloxacin conjugates self-assembled into nanowires of ∼30 nm diameters while HEC–moxifloxacin conjugates self-assembled into nanoparticles of 150–350 nm. In vitro drug release studies revealed that 15 and 49% moxifloxacin release occurred from the HPC–moxifloxacin conjugate after 6 h at pH 1.2 and 7.4, respectively. Similarly, moxifloxacin release from HEC–moxifloxacin conjugates was 15 and 39% at pH 1.2 and 7.4, respectively. Bioavailability and pharmacokinetic studies in rabbits showed that both HPC- and HEC-conjugates exhibited significantly enhanced moxifloxacin plasma half-life, over 24 h, confirming sustained release and enhanced bioavailability (AUC 2.0–2.1 times higher) of moxifloxacin.